Analisis Pendistribusian Zakat pada Lembaga Badan Amil Zakat - Agil Bahsoan; Fadlan Hamzah; Rahmat M Bidalo; Mohammad Fadly Karim; Putri Rizki Amanda (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to find out how the distribution of zakat by Baznas in Gorontalo Province. This research uses empirical research using a qualitative descriptive approach. Data collection techniques used are observation, interviews, and documentation. The results of the study show that the distribution of zakat by Baznas in Gorontalo Province is divided into four programs, namely productive economic programs, health programs, education programs, humanitarian programs and location charges.